Studies on the Formation of Mullite from Diphasic Al2O3-SiO2 Gel by Fourier Transform Infrared Spectroscopy - Jagannath Roy; Narayan Bandyopadhyay; Santanu Das; Saikat Maitra (Iranian Journal of Chemistry & Chemical Engineering, 2011)
Al2O3-SiO2 diphasic gel was synthesized by sol gel route from aluminium nitrate and silicic acid following aqueous phase colloidal interaction. The precursor gel powder was thoroughly characterized by chemical analysis, measurement of surface area and bulk density measurement. The gel powder was further characterized by thermogravimetry, XRD diffraction study of the heat treated samples and Scanning Electron Microscopic (SEM) study of the fractured surfaces of the heat treated compacts. The gel was observed to be a truly di-phasic in nature and was capable of forming nano-structured well distributed mullite phase in the microstructure of the heat treated sample. The gel powder was heated at different temperatures and the formation of Al-O-Si linkage towards the formation of mullite phase (3Al2O3 , 2SiO2) was studied by Fourier Transform Infra Red (FT-IR) spectroscopy. The characteristic Al-O-Si linkage was found to develop after 600oC indicating the formation of mullite gel  and at 16000oC the linkage became very strong indicating complete crystallization of mullite.